2012
DOI: 10.1542/peds.2012-1029d
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Associations Between Teen Dating Violence Victimization and Adverse Health Outcomes

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Although a number of crosssectional studies have documented associations between teen dating violence victimization and adverse health outcomes, including sexual risk behaviors, suicidality, substance use, and depression, longitudinal work examining the relationship between victimization and outcomes is limited. WHAT THIS STUDY ADDS:This study is the first to demonstrate the longitudinal associations between teen dating violence victimization and multiple young adult health outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(52 reference statements)
0
2
0
Order By: Relevance
“…Consistent with previous research (Scott et al, 2010), childhood physical abuse is detrimental to long-term mental health. Moreover, while most DV research has focused on adverse mental health as an outcome of DV (Chan et al, 2008;Exner-Cortens et al, 2013), our study showed that young adults who suffer from adverse mental health, PTSD specifically, have a higher likelihood of experiencing and perpetrating DV as well.…”
Section: Indirect Effects Via Anxiety Ptsd and Depressive Symptomsmentioning
confidence: 63%
See 1 more Smart Citation
“…Consistent with previous research (Scott et al, 2010), childhood physical abuse is detrimental to long-term mental health. Moreover, while most DV research has focused on adverse mental health as an outcome of DV (Chan et al, 2008;Exner-Cortens et al, 2013), our study showed that young adults who suffer from adverse mental health, PTSD specifically, have a higher likelihood of experiencing and perpetrating DV as well.…”
Section: Indirect Effects Via Anxiety Ptsd and Depressive Symptomsmentioning
confidence: 63%
“…Further, we included age, gender, and race as control variables since research has shown that both DV and mental health often vary by these demographic factors (Alleyne-Green, Coleman-Cowger, & Henry, 2012;Shorey, Cornelius, & Bell, 2008;Twenge & Nolen-Hoeksema, 2002). We also controlled for prior physical DV victimization and perpetration because of the association between DV and mental health (Exner-Cortens et al, 2013), as well as the link between prior DV experiences and future DV (Jouriles, Choi, Rancher, & Temple, 2017). Figure 1, we hypothesized that childhood physical abuse would be directly linked to adverse mental health, and adverse mental health would directly associate with physical DV victimization and perpetration.…”
Section: The Present Studymentioning
confidence: 99%